Oxygen and hydrogen profiles and electrical properties of unintentionally doped gallium nitride grown by hydride vapor phase epitaxy. Issue 6 (7th May 2015) - Garbe, Valentin; Abendroth, Barbara; Stöcker, Hartmut; Gavrilov, Arkadi; Cohen‐Elias, Doron; Mehari, Shlomo; Ritter, Dan; Meyer, Dirk C.
<x xml:space="preserve">Abstract</x> Utilizing electrical, structural and optical methods, a doping model of an unintentionally doped n‐GaN wafer was drawn up, containing two different GaN layers. The smooth GaN surface layer exhibits lower carrier concentration but higher mobility, while the bottom layer shows higher background carrier concentration and lower mobility, because of high impurity incorporation. Oxygen seems to be the donor, while substitutionally filling the positions of nitrogen vacancies, leading to n‐doping.